Resultados de la asignatura propedéutica clínica en el 5to semestre de la carrera de medicina. Curso 2006-2007 Results obtained in the subject "Clinical Propedeutics". Fifth term of Medical Studies. Academic course 2006 -2007 - García Fernández, Ilia; Valdés Vento, Ana Carmen; Fortún Prieto, Adalberto; Paz Paula, Eduardo; Delgado Rodríguez, Ariel E. (Revista de Ciencias Médicas de Pinar del Río, 2012)
Se realizó un estudio observacional, descriptivo y transversal sobre los resultados obtenidos por los estudiantes de 3er año de la carrera de Medicina en la asignatura Propedéutica Clínica durante el 5to semestre de la carrera de Medicina del curso 2006- 2007, con el objetivo de exponer dichos resultados, teniendo en cuenta los diferentes modelos de enseñanza donde se encuentran insertados. Para ello fue necesario el análisis de las evaluaciones, tanto de los que se encuentran en el PROYECTO POLICLÍNICO UNIVERSITARIO como de los del modelo tradicional y experimental en el que participó un número menor de estudiantes. Además se recogieron los criterios y recomendaciones de los estudiantes y Profesores Integrales que imparten esta asignatura. Los datos fueron recogidos de las actas entregadas y de los registros de asistencia y control a clases, además de una encuesta aplicada a estudiantes y profesores que se encuentran recibiendo e impartiendo la asignatura. Los resultados fueron presentados en tablas y gráficos. Como resultados de nuestra investigación obtuvimos que los estudiantes que recibieron la asignatura en la APS con los profesores integrales obtuvieran calificaciones similares a los que la recibieron por el Método Tradicional, con una tendencia a mejores resultados. Los estudiantes encuestados que se encuentran en el Proyecto Policlínico Universitario recibiendo la asignatura manifestaron su total satisfacción con el Proyecto y refieren continuar en el mismo. Los profesores que imparten la Propedéutica Clínica, se encuentran en total disposición de continuar impartiéndola en cursos posteriores. Palabras clave: ESTUDIANTES DE MEDICINA, ESCUELAS MÉDICAS, PRÁCTICA DE GRUPO, ENSEÑANZA/métodos, EDUCACIÓN MÉDICA. ABSTRACT An observational, descriptive and cross-sectional study about the results obtained for medical students being currently in the 3rd. academic year, and taking the subject "Clinical propedeutics" during the 5th. term of the academic course 2006-2007 was conducted with the purpose of showing these results and taking into account the different teaching models where these students are enrolled. It was necessary to analyze the evaluations of those students enrolled in the important experience of the University Outpatient Clinic Project, besides those in the same term, but enrolled in the model of traditional medical studies. Data also showed another third model (called "experimental"), recording the participation of a minor group of these students. In the study those criteria, recommendations and projections of the students were gathered, as well as the opinions of professors (specialists and residents in Comprehensive Medicine), who teach the subject in Primary Health Care. Data studied were collected from the official documents at the Department of Medical Studies, and from the records of attendance and control to lectures. Besides, a survey was applied to students taking the subject and professors teaching it on the settling of Primary health Care, these results were recorded in tables and charts. The results of the research were: Those students who took the subject in the setting of Primary Health Care with comprehensive professors obtained similar grades as those in the traditional method, having those from the Primary Health Care a trend to better results. Students inquired in the University Outpatient Clinic Project who were taking the subject expressed satisfaction with the project, and the majority will continue in this model of medical studies to take the rest of the subjects, Those professors teaching Clinical Propedeutics in Primarty Health Care are prepared to teach the same subject in future academic courses. Key words: MEDICAL STUDENTS, MEDICAL SCHOOOLS, PRACTICE OF GROUP, TEACHING/methods, MEDICAL EDUCATION.